Functional Characterization of ABCC Proteins from Trypanosoma cruzi and Their Involvement with Thiol Transport - da Costa, Kelli Monteiro; Valente, Raphael C.; Salustiano, Eduardo J.; Gentile, Luciana B.; Freire-de-Lima, Leonardo; Mendonça-Previato, Lucia; Previato, José O. (Frontiers in Microbiology, 2018)
Chagas disease is a neglected disease caused by the protozoan Trypanosoma cruzi and affects 8 million people worldwide. The main chemotherapy is based on benznidazole. The efficacy in the treatment depends on factors such as the parasite strain, which may present different sensitivity to treatment. In this context, the expression of ABC transporters has been related to chemotherapy failure. ABC transporters share a well-conserved ABC domain, responsible for ATP binding and hydrolysis, whose the energy released is coupled to transport of molecules through membranes. The most known ABC transporters are ABCB1 and ABCC1, involved in the multidrug resistance phenotype in cancer, given their participation in cellular detoxification. In T. cruzi, 27 ABC genes were identified in the genome. Nonetheless, only four ABC genes were characterized: ABCA3, involved in vesicular trafficking; ABCG1, overexpressed in strains naturally resistant to benznidazole, and P-glycoprotein 1 and 2, whose participation in drug resistance is controversial. Considering P-glycoprotein genes are related to ABCC subfamily in T. cruzi according to the demonstration using BLASTP alignment, we evaluated both ABCB1-like and ABCC-like activities in epimastigote and trypomastigote forms of the Y strain. The transport activities were evaluated by the efflux of the fluorescent dyes Rhodamine 123 and Carboxyfluorescein in a flow cytometer. Results indicated that there was no ABCB1-like activity in both T. cruzi forms. Conversely, results demonstrated ABCC-like activity in both epimastigote and trypomastigote forms of T. cruzi. This activity was inhibited by ABCC transport modulators (probenecid, indomethacin and MK-571), by ATP-depleting agents (sodium azide and iodoacetic acid) and by the thiol-depleting agent N-ethylmaleimide. Additionally, the presence of ABCC-like activity was supported by direct inhibition of the thiol-conjugated compound efflux with indomethacin, characteristic of ABCC subfamily members. Taken together, the results provide the first description of native ABCC-like activity in T. cruzi epimastigote and trypomastigote forms, indicating that the study of the biological role for that thiol transporter is crucial to reveal new molecular mechanisms for therapeutic approaches in the Chagas disease.